(untitled) (Research, Society and Development, 2020)
Agrosilvopastoral system is a type of production that involves the soil-forage-animal interface, both of which are benefited by the system. Hence, the present study evaluated the effects of agrosilvopastoral system on the quantitative and qualitative characteristics from pasture, and the animal performance during the feeding period of Nellore heifers. The treatments included: Soil-forage-animal – 357 eucalyptus trees per hectare (LFA14x2m); Soil-forage-animal – 227 eucalyptus trees per hectare (LFA22x2m); and Soil-animal – Five native trees remaining per hectare (CON). The forage used was Brachiaria brizantha cv. BRS Piatã and having as trees planted the Eucalyptus urograndis clones H 13. Treatment effects (P <0.05) for forage accumulation and pasture height, which were lowest in LFA14x2m compared to the others. Total forage dry mass in CON treatment was significantly greater (P <0.05) compared to the other treatments, showing maximum production in March. The LFA14x2m treatment was favorable for greater forage quality, showing an effect on chemical composition (P <0.05), compared to other treatments. Whereas, in November the LFA22x2m treatment was better for neutral detergent fiber. January and March, the treatments were similar (P >0.05) for average daily gain, while in November period, LFA14x2m treatment showed the lowest value (P <0.05). The lowest weight gain by area (November) occurred in the LFA14x2m treatment (P <0.05), although in March the LFA14x2m treatment stocking rate was similar to the others. Forage production and animal performance are altered by the trees densification in agrosilvopastoral systems. The chemical composition of pasture is better in systems with a higher trees density.